Positions on the mat : a micro-ethnographic study of teachers' and learners' co-construction of an early literacy practice - Van der Mescht, Caroline (Rhodes University, Faculty of Education, Department of Education, 2013)
This thesis reports on research into micro-interactions within the reading literacy event Reading on the Mat in three Grade One classrooms. This event is the core of literacy learning in Foundation Phase classrooms in formerly 'white', government-funded primary schools in the Eastern Cape, South Africa, and takes place daily for every child. It is literacy practice resembling Group Guided Reading. The research focused on teachers' identity-forming decisions, actions and discourses as a way of examining microinteractions within the literacy event. Hymes's work on the ethnography of communication provided categories for the investigation. Using an ethnographic approach, I entered the sites of the study as a participant observer. There I focused on the central literacy event, in which a group of children and the teacher sit in close proximity. I made field notes, video recordings and audio recordings in three sets of visits spanning the full school year. These were supplemented by teacher interviews, consideration of reports and assessments, and an analysis of the text types used on the Mat, for example, graded readers, flash cards and phonics primers. Beginning with Hymes' S.P.E.A.K.I.N.G. mnemonic, cycles of analysis using multiple instruments foregrounded the data. The central finding of this research is that in Reading on the Mat children are offered identities through strong normative work and embedded practices. Teachers promote positive identities for children as successful readers and create positive affect for reading activities. This positive positioning work is however undercut by three factors: first, the fact that activities on the Mat focus on decoding text fragments rather than interrogating whole texts. The resultant identity offered to children is one of code breakers alone. A finding subsidiary to this, but important for pedagogic practice, is that teachers' choice of text types is the most powerful determinant of children's code breaker identity. A second factor that undercuts children's identity as successful readers is that, although they are active, they have little agency. This derives from the strong assessment focus of teachers on the Mat and their questioning practices. A third factor which undercuts the positive identity children are offered in this literacy event is that, by focusing primarily on decoding fragmented text and on assessment opportunities, teachers avoid engaging with issues of differentiation and disregard cultural and linguistic differences. Teachers' choices, therefore, while creating a positive climate in the classroom and developing emergent readers who are effective decoders, construct children as limited literate subjects. The same choices enable teachers to ignore learner diversity.,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Literacy -- Study and teaching (Primary) -- South Africa -- Eastern Cape; English language -- Study and teaching (Primary) -- South Africa -- Eastern Cape; English literature -- Study and teaching (Primary) -- South Africa -- Eastern Cape; Education, Primary -- Research -- South Africa -- Eastern Cape; Teachers -- Psychology; Language and culture